ANALISA PENDIDIKAN ISLAM INKLUSIF UNTUK ANAK BERKEBUTUHAN KHUSUS - Syarniah; Husnul Yaqin; Syaifuddin Sabda; Ridhahani Fidzi (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
Children with special needs are children who are classified as disabled or who have disabilities, as well as potential and talented children. In accordance with the mandate of the 1945 Constitution Chapter XA on human rights, every person has the right to obtain and choose education, the right to be free from discriminatory treatment and every child has the right to protection from violence and discrimination. The implication of this 1945 Constitution mandate is the existence of inclusive education. Inclusive education for children with special needs is an innovative educational method strategy that seeks to eliminate discrimination and provide equitable educational opportunities for these children. The purpose of this research is to analyze Islamic education in inclusive education for children with special needs. This research method is a literature review or library research with a qualitative descriptive approach. The results of the analysis concluded that inclusive Islamic education is very supportive for the implementation of equitable education without discrimination for children with special needs.